Sparks of the logos : essays in rabbinic hermeneutics - Boyarin, Daniel (Brill reference library of Judaism, 2003)
This work covers the typological relation of rabbinic Judaism to Christianity, and provides a re-examination, by going back to the roots, of a rabbinic Judaism that would not manifest some of the deleterious social ideologies and practices that modern orthodox Judaism generally does.